2021
DOI: 10.1038/s41541-021-00392-7
|View full text |Cite
|
Sign up to set email alerts
|

A SARS-CoV-2 spike ferritin nanoparticle vaccine protects hamsters against Alpha and Beta virus variant challenge

Abstract: The emergence of SARS-CoV-2 variants of concern (VOC) requires adequate coverage of vaccine protection. We evaluated whether a SARS-CoV-2 spike ferritin nanoparticle vaccine (SpFN), adjuvanted with the Army Liposomal Formulation QS21 (ALFQ), conferred protection against the Alpha (B.1.1.7), and Beta (B.1.351) VOCs in Syrian golden hamsters. SpFN-ALFQ was administered as either single or double-vaccination (0 and 4 week) regimens, using a high (10 μg) or low (0.2 μg) dose. Animals were intranasally challenged a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 32 publications
1
59
0
1
Order By: Relevance
“…Herein, we describe the results of a statistically-balanced nonhuman primate study in which we evaluated the efficacy of SARS-CoV-2 SpFN protein nanoparticle vaccine against a robust and high-titer SARS-CoV-2 respiratory (IT) and mucosal (IN) challenge. Efficacy and/or immunogenicity of this vaccine has been demonstrated in mice, hamsters, and rhesus macaques [17, 19, 31], including efficacy against the Alpha and Beta variants of SARS-CoV-2 demonstrated in hamsters [19]. CM were chosen for the present study as this model reproduces several human disease characteristics and provides two ideal objective and relevant endpoint criteria for efficacy evaluations: fever and viral RNA in nasopharyngeal swabs [20, 21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we describe the results of a statistically-balanced nonhuman primate study in which we evaluated the efficacy of SARS-CoV-2 SpFN protein nanoparticle vaccine against a robust and high-titer SARS-CoV-2 respiratory (IT) and mucosal (IN) challenge. Efficacy and/or immunogenicity of this vaccine has been demonstrated in mice, hamsters, and rhesus macaques [17, 19, 31], including efficacy against the Alpha and Beta variants of SARS-CoV-2 demonstrated in hamsters [19]. CM were chosen for the present study as this model reproduces several human disease characteristics and provides two ideal objective and relevant endpoint criteria for efficacy evaluations: fever and viral RNA in nasopharyngeal swabs [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the immunogenicity of SpFN adjuvanted with either aluminum hydroxide (AlOH3) or Army Liposomal Formulation QS-21 (ALFQ) in mice, and observed increased humoral and T cell responses with ALFQ [17]. Subsequent vaccine efficacy studies of SpFN-ALFQ demonstrated protection against disease and viral replication in the respiratory tract of Syrian golden hamsters, and against viral replication in rhesus macaques [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…RBD monomer, dimer and trimer antigens elicited potent Ab responses 9, 10, 13 , while highly ordered and repetitive structures of RBDs mimicked the organization and density of antigens on natural virions, to be of great advantage in promoting protective immunity 17, 46, 47 . Self-assembling multivalent RBD or spike nanoparticles using SpyTag/SpyCatcher or sortase-mediated ligation and computationally designed scaffolds, ferritin, or lumazine synthase fusion platforms have shown high potentiation of immune responses against COVID-19 1719, 47, 48 . However, administration of homotypic multivalent antigens or possibly multiple booster doses with strain-specific antigens can lead to over-specialization of the B cells with limited breadth of antigen recognition 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, nAbs against multiple variants are currently accepted as a correlate of protection 12, 37 , and the RBD indeed accounts for more than 90% of the neutralizing activity in sera from COVID-19 convalescent and vaccinated individuals 912 . RBD monomer, dimer and trimer antigens elicited potent Ab responses 9, 10, 13 , while highly ordered and repetitive structures of RBDs mimicked the organization and density of antigens on natural virions, to be of great advantage in promoting protective immunity 17, 46, 47 . Self-assembling multivalent RBD or spike nanoparticles using SpyTag/SpyCatcher or sortase-mediated ligation and computationally designed scaffolds, ferritin, or lumazine synthase fusion platforms have shown high potentiation of immune responses against COVID-19 1719, 47, 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The development of candidate vaccines based on protein assemblies is a powerful strategy. Ferritin self-assembled NPs are already in clinical trials as nasal nanovaccines [ 68 ] ( Table 1 ).…”
Section: Nanovaccinesmentioning
confidence: 99%